Students’ Speaking Anxiety in English Class - Atanasius Gabe Hardional Sinaga; Syahrial Syahrial; Gita Mutiara Hati (Yayasan Karinosseff Muda Indonesia, 2020)
This research aimed to find out the level of students’ speaking anxiety students in English class and the most dominant factors that caused students’ speaking anxiety faced by the third grade students of Junior High School in SMPN 15 Bengkulu in English Classroom. This research used descriptive quantitative design with questionnaire as the instrument. The questionnaire of this research was Foreign Language Classroom Anxiety Scale (FLCAS) proposed by Horwitz et al. (1983). The data has been analyzed by using SPSS program. The population of this research was the third grade students in SMPN 15 Bengkulu. The total is 7 classes: class A, Class B, Class C, Class D, Class E, Class F, and Class G. The total number of population is 163 students. From 7 classes, the researcher decided to take only 20% of student each. The result of this research showed that the majority of the students of the third-grade were Mildly Anxious level and the most dominant factors causing the student speaking anxiety was the Fear of Negative Evaluation. According to the result, most of the students were already feel anxious about the fact that they had to speak in a group or individually and also being evaluated by the teacher in front of the English class. In conclusion, the researcher found that students are afraid to speak up in front of the class because they always think that other students will laugh at them and judge the student who speaks in front of the class. This might make the student’s speaking anxiety arise and make them to stay silent instead of speaking.